Seven Novel Genes Related to Cell Proliferation and Migration of VHL-Mutated Pheochromocytoma - Gao, Shuai; Liu, Longfei; Li, Zhuolin; Pang, Yingxian; Shi, Jiaqi; Zhu, Feizhou (Frontiers in Endocrinology, 2021)
Pheochromocytoma, as a neuroendocrine tumor with the highest genetic correlation in all types of tumors, has attracted extensive attention. Von Hipper Lindau (VHL) has the highest mutation frequency among the genes associated with pheochromocytoma. However, the effect of VHL on the proteome of pheochromocytoma remains to be explored. In this study, the VHL knockdown (VHL-KD) PC12 cell model was established by RNA interference (shRNA). We compared the proteomics of VHL-KD and VHL-WT PC12 cell lines. The results showed that the expression of 434 proteins (VHL shRNA / WT > 1.3) changed significantly in VHL-KD-PC12 cells. Among the 434 kinds of proteins, 83 were involved in cell proliferation, cell cycle and cell migration, and so on. More importantly, among these proteins, we found seven novel key genes, including Connective Tissue Growth Factor (CTGF), Syndecan Binding Protein (SDCBP), Cysteine Rich Protein 61 (CYR61 / CCN1), Collagen Type III Alpha 1 Chain (COL3A1), Collagen Type I Alpha 1 Chain (COL1A1), Collagen Type V Alpha 2 Chain (COL5A2) and Serpin Family E Member 1 (SERPINE1)2, were overexpressed and simultaneously regulate cell proliferation and migration in VHL-KD PC12 cells. Furthermore, the abnormal accumulation of HIF-2α caused by VHL-KD significantly increased the expression of these seven genes during hypoxia. Moreover, cell-counting, scratch and transwell assays demonstrated that VHL-KD could promote cell proliferation and migration, and change cell morphology. These findings indicated that inhibition of VHL expression can promote the development of pheochromocytoma by activating the expression of cell proliferation and migration associated genes.